Uvod v razumevanje upravnega prava in javne uprave - Tičar, Bojan (University of Maribor Press, 2019)
1st reprint of 1st editon Introduction to Understanding Public Law and Public Administration. The present book is intended for anyone interested in the public sector, administrative law, and public administration and the concepts thereof, including experts that apply institutions from these fields in their daily work. The monograph is written in such a way that it should be understandable to every reader. The monograph presents essential elements of law and administrative law in particular, as well as the position of natural persons who work in public administration. The concept and functions of public administration are defined. Concepts are described in a comprehensible manner, as the objective of the monograph is that readers come to understand the essential elements of the treated subjects. The monograph is divided into three parts. The first part contains an introduction to law and administrative law in general. Basic legal concepts and their development as well as fundamental institutions of administrative law, which can be divided into substantive and formal aspects, are explained. The practical application of formal, i.e. procedural law, is presented in more detail with an outline of the fundamental institutions regulating general administrative procedure. The presentation focuses on parties and persons liable when exercising their substantive and procedural rights in cases in which their interest is in actual or potential conflict with the public interest. The second part presents public administration as a special legal phenomenon. First, it is presented from an organisational point of view, and second, from a functional point of view. From an organisational point of view, public administration is part of the public sector that has a particular sector classification of legal entities. The sector classification of legal entities developed in the monograph entails original work of the authors and its objective is to provide a clearer delimitation of the public sector than is regulated in Slovenian legislation. Thereafter, the phenomenon of public administration is presented functionally through its three main functions: (1) authoritative/regulatory, (2) service, and (3) acceleration. Within the framework of the first element, the following concepts are analysed: state administration, local self-government, and bearers of public authority; within the framework of the second element: providers of public utility services and non-commercial public services; and within the framework of the third element: public funds and public-private partnerships. The third part of the monograph discusses the legal position of natural persons who work in public administration and the public sector. First, the legal position of public officials and fundamental institutions regarding their integrity from the perspective of the prevention of corruption are analysed. Thereafter, the differences between officials and civil servants are outlined and the legal position of civil servants explored. Civil servants are divided into two groups: those employed within the entire public sector and those holding the post of an official and ancillary posts. The monograph concludes with a systematic analysis of the elements of the salary system in the public sector that is used for both public officials and civil servants.